Is There Asymmetry Between the Concave and Convex Pedicles in Adolescent Idiopathic Scoliosis? A CT Investigation. Issue 3 (March 2017) - Davis, Colin M.; Grant, Caroline A.; Pearcy, Mark J.; Askin, Geoffrey N.; Labrom, Robert D.; Izatt, Maree T.; Adam, Clayton J.; Little, Paige J.
Abstract: Background: Adolescent idiopathic scoliosis is a complex three‐dimensional deformity of the spine characterized by deformities in the sagittal, coronal, and axial planes. Spinal fusion using pedicle screw instrumentation is a widely used method for surgical correction in severe (coronal deformity, Cobb angle > 45°) adolescent idiopathic scoliosis curves. Understanding the anatomic difference in the pedicles of patients with adolescent idiopathic scoliosis is essential to reduce the risk of neurovascular or visceral injury through pedicle screw misplacement. Questions/Purposes: To use CT scans (1) to analyze pedicle anatomy in the adolescent thoracic scoliotic spine comparing concave and convex pedicles and (2) to assess the intra‐ and interobserver reliability of these measurements to provide critical information to spine surgeons regarding size, length, and angle of projection. Methods: Between 2007 and 2009, 27 patients with adolescent idiopathic scoliosis underwent thoracoscopic anterior correction surgery by two experienced spinal surgeons. Preoperatively, each patient underwent a CT scan as was their standard of care at that time. Twenty‐two patients (mean age, 15.7 years; SD, 2.4 years; range, 11.6‐22 years) (mean Cobb angle, 53°; SD, 5.3°; range, 42°‐63°) were selected. Inclusion criteria were a clinical diagnosis of adolescent idiopathic scoliosis, female, and Lenke type 1 adolescent idiopathic scoliosis with the major curve confined to the thoracic spine. Using three‐dimensional image analysis software, the pedicle width, inner cortical pedicle width, pedicle height, inner cortical pedicle height, pedicle length, chord length, transverse pedicle angle, and sagittal pedicle angles were measured. Randomly selected scans were remeasured by two of the authors and the reproducibility of the measurement definitions was validated through limit of agreement analysis. Results: The concave pedicle widths were smaller compared with the convex pedicle widths at T7, T8, and T9 by 37% (3.44 mm ± 1.16 mm vs 4.72 mm ± 1.02 mm; p < 0.001; mean difference, 1.27 mm; 95% CI, 0.92 mm‐1.62 mm), 32% (3.66 mm ± 1.00 mm vs 4.82 mm ± 1.10 mm; p < 0.001; mean difference, 1.16 mm; 95% CI, 0.84 mm‐1.49 mm), and 25% (4.10 mm ± 1.57 mm vs 5.12 mm ± 1.17 mm; p < 0.001; mean difference, 1.02 mm; 95% CI, 0.66 mm‐1.39 mm), respectively. The concave pedicle heights were smaller than the convex at T5 (9.43 mm ± 0.98 vs 10.63 mm ± 1.10 mm; p = 0.002; mean difference, 1.02 mm; 95% CI, 0.59 mm‐1.45 mm), T6 (8.87 mm ± 1.37 mm vs 10.88 mm ± 0.81 mm; p < 0.001; mean difference, 2.02 mm; 95% CI, 1.40 mm‐2.63 mm), T7 (9.09 mm ± 1.24 mm vs 11.35 mm ± 0.84 mm; p < 0.001; mean difference, 2.26 mm; 95% CI, 1.81 mm‐2.72 mm), and T8 (10.11 mm ± 1.05 mm vs 11.86 mm ± 0.88 mm; p < 0.001; mean difference, 1.75 mm; 95% CI, 1.30 mm‐2.19 mm). Conversely, the concave transverse pedicle angle was larger than the convex at levels T6 (11.37° ± 4.48° vs 8.82° ± 4.31°; p = 0.004; mean difference, 2.54°; 95% CI, 1.10°‐3.99°), T7 (12.69° ± 5.93° vs 8.65° ± 3.79°; p = 0.002; mean difference, 4.04°; 95% CI, 1.90°‐6.17°), T8 (13.24° ± 5.28° vs 7.66° ± 4.87°; p < 0.001; mean difference, 5.58°; 95% CI, 2.99°‐8.17°), and T9 (19.95° ± 5.69° vs 8.21° ± 4.02°; p < 0.001; mean difference, 4.74°; 95% CI, 2.68°‐6.80°), indicating a more posterolateral to anteromedial pedicle orientation. Conclusions: There is clinically important asymmetry in the morphologic features of pedicles in individuals with adolescent idiopathic scoliosis. The concave side of the curve compared with the convex side is smaller in height and width periapically. Furthermore, the trajectory of the pedicle is more acute on the convex side of the curve compared with the concave side around the apex of the curve. Knowledge of these anatomic variations is essential when performing scoliosis correction surgery to assist with selecting the correct pedicle screw size and trajectory of insertion to reduce the risk of pedicle wall perforation and neurovascular injury.